The Book Market in the Light of Paratexts of Printed Books in the Kyiv Metropolitanate: Selected Issues - Nowak, Alicja Zofia (Senoji Lietuvos literatūra, 2025)
The article deals with selected issues concerning the functioning of the publishing market in the Kyiv metropolitanate in the first decades after the first Ruthenian typographers became active (up to the mid-seventeenth century). The source base is the paratexts (the preface, the dedicatory letter, the afterword) of books of mainly liturgical and more broadly Orthodox use dominating the books on offer, whose authors were mostly publishers, printers, and editors, acting independently or as members of teams developing the publishing process. In the paratexts, they attempted to explain the reasons for their publishing activity or justify the choice of a particular book. Among the most frequent reasons, they would point out errors occurring in manuscript books, the scarcity or unavailability of particular books caused by various factors, the existence of printed versions but not corrected within the scope of issues concerning liturgical and sacramental-ceremonial practice. In addition, the paratexts contain interesting data on the competition between various printing centres, indicating the difficulties in coordinating and controlling the publishing market by the Metropolitan of Kyiv. The paratextual material also brings interesting evidence on the existence of an in-depth reflection on the role of printing, the importance of books in religious life and in the process of expanding knowledge in the Ruthenian environment in the Polish-Lithuanian Commonwealth.